2020
DOI: 10.1111/1462-2920.15206
|View full text |Cite
|
Sign up to set email alerts
|

Differential distribution and proteomic response of Saccharomyces cerevisiae and non‐model yeast species to zinc

Abstract: Summary Zinc surplus in yeast cells has been previously investigated thanks to transcriptomic studies by using traditionally Saccharomyces cerevisiae as a model. However, proteome response under zinc‐replete conditions needs to be further studied in yeast. For that reason, eight yeast strains from seven different species were inoculated in zinc‐depleted and zinc‐replete media. The quantitative and qualitative comparative label‐free proteomic analysis enabled the identification of between 2000 and 3000 proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Many studies justify the different behavior not only among different genera but also at strain level. García-Bejar et al [32] , observed that the response of two strains from the same specie (FR19 and ECF61-Diutinia rugosa), revealed slight differences in the proteome alteration in response to stress conditions. Similar results were found in other works related to different strains of S. cerevisiae also under stress conditions [33] or related to the cell wall proteomic profile of fungi [34] .…”
Section: Resultsmentioning
confidence: 99%
“…Many studies justify the different behavior not only among different genera but also at strain level. García-Bejar et al [32] , observed that the response of two strains from the same specie (FR19 and ECF61-Diutinia rugosa), revealed slight differences in the proteome alteration in response to stress conditions. Similar results were found in other works related to different strains of S. cerevisiae also under stress conditions [33] or related to the cell wall proteomic profile of fungi [34] .…”
Section: Resultsmentioning
confidence: 99%
“…rugosa and W . sorbophila , a previous study analysed the zinc‐associated changes to the proteome (García‐Béjar et al ., 2020c); however, no specific analysis for the cell wall–related proteins was carried out.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above theory, by overexpressing the pyruvate carboxylase gene and deleting the phosphoenolpyruvate carboxykinase gene, the replenishment of oxaloacetate used for the TCA cycle and the fixation of CO 2 can be enhanced, which has the potential to further improve mycoprotein synthesis. Additionally, zinc, an indispensable cofactor for many transcription factors and enzymes, has been resoundingly applied in fungi, such as Saccharomyces cerevisiae, to improve biomass yield and protein content. However, similar studies have not been reported in F. venenatum.…”
Section: Introductionmentioning
confidence: 99%